Enterrado en vida - Bennett, Arnold, 1867-1931; Vera, Vicente, 1855-1934; Vales, José C., 1965-; Pelayo, Jesús J.; Bennett, Arnold, 1867-1931. (Madrid : Impedimenta, 2013)
In this funny tale, Henry Leek, valet to the renowned painter Priam Farll, dies and they are mistakenly identified as the other. The valet is buried with pomp and circumstance in Westminster Abbey while Priam poses as Leek.
Online resource; title from ePub title page (Digitalia, viewed February 18, 2018)
Keywords: Painters -- England -- Fiction; Valets -- England -- Fiction; Role reversal -- Fiction; Impersonation -- Fiction; England -- Juvenile fiction; Detective and mystery fiction; Electronic books